To be committed or not: examining effects of personal and workplace variables on the organizational commitment of Southern prison staff - Lambert, Eric G. (Criminal justice studies, 2017)
This study examined how personal and workplace variables were related to organizational commitment among staff working at a large Southern prison. The personal variables were gender, age, position, tenure, educational level, and supervisory status. The workplace variables were assessment of training, job variety, role clarity, input into decision-making, and instrumental communication. The results indicate workplace variables play a greater role in shaping affective commitment of surveyed Southern prison staff than do personal variables. The personal variables explained only 10% of the variance in the commitment index, while workplace factors accounted for approximately 59% of the variance and were significant determinants of organizational commitment among the respondents. In the multivariate regression analysis, age, assessment of training, job variety, role clarity, input into decision-making, and instrumental communication all had positive associations with commitment. Educational level had a negative relationship with commitment. Implications of these findings for policy and future research are also discussed.